The effect of vancomycin doses greater than 2 grams on serum creatinine and vancomycin trough levels - Mansour, Hanine (2014)
Objective: To assess the effect of vancomycin doses greater than 2 grams on renal function and vancomycin trough levels Methods: This is a retrospective, pharmacokinetic study performed in a tertiary care level II trauma center. 3579 electronic charts of patients who received vancomcyin at the medical facility between January 2010 and December 2011 were reviewed. Only 30 patients met the inclusion criteria of the study. Included patients were those who were at least 18 years of age who received doses greater than 2 grams of vancomycin for at least 48 hours. Patients in the intensive care units, pregnant or on hemodialysis and were not included in the study. The mean weight for the participants was 154.67 kg. Results: Patients were dosed based on the institution’s vancomycin dosing protocol such as 15-20 mg/kg per dose where the frequency was determined based on the estimated creatinine clearance using cockroft gault equation. A loading dose of 25-30 mg/kg was administered in few cases. Two out of thirty subjects had shown an increase of serum creatinine of ≥ 0.3mg/dL when receiving maintenance doses greater than 2 grams of vancomycin. A Z approximation test was used where a standard error of 0.043 with an α error equal to 0.05 and a 95% confidence interval of (-0.024-0.144) were found. The use of doses greater than 2 grams of IV vancomycin did not show a statistically significance increase in serum creatinine. The two subjects who did have a significant increase in serum creatinine were receiving concomitant nephrotoxins. Conclusion: The use of doses greater than 2 grams of IV vancomycin did not show a statistically significant increase in serum creatinine. Patients whom serum creatinine increased were on other nephrotoxin agents that could have contributed to the acute kidney injury that was seen in these patients.